Makna Tersembunyi di Balik Simbol: Kajian Semiotika menurut Charles Sanders Peirce dalam Puisi “Ketika Burung Merpati Sore Melayang” Karya Tauqik Ismail - Febriana, Cindy; Paputungan, Leoni; Hidayanti Ali, Ayu; Umam Kau, Munkizul (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study analyzes the poem "When the Evening Dove Floats" by Taufiq Ismail using Charles Sanders Peirce's semiotic approach. The poem represents the condition of Indonesia during a multidimensional crisis, both social, political, and natural. Through the analysis of Peirce's triad of signs (representamen, object, interpretan), this study identifies key symbols such as "the sky of morals that collapses," natural disasters, the Trisakti event, and "the evening dove floats." These symbols are studied to reveal their literal and connotative meanings, as well as various interpretations that may arise. The results of the analysis show that the poem reflects the poet's deep concern for moral collapse, injustice, violence, and the suffering of the people. The symbol "the dove" shows fragile hope amidst the sadness. This study concludes that the poem "When the Evening Dove Floats" is a sharp reflection of the socio-political conditions of Indonesia at the time of its creation, and shows the power of poetry in representing complex socio-political realities.